Clinical screening of oropharyngeal dysphagia: standard of care. Issue 2 (31st August 2017) - Caviedes, Ivan; Fernandez-Bussy, Sebastian; Labarca, Gonzalo; Herth, Felix J.F.
We read with interest the paper by Verin et al. [1] related to oropharyngeal dysphagia and its importance in institutionalised neurological and head and neck patients, between others. Furthermore, this is a very common problem in the critical and intermediate care settings, and a similar situation occurs with other acute neurological diseases, such as amyotrophic lateral sclerosis, cerebral trauma, post-neurosurgical procedures and toxic metabolic encephalopathies [2, 3]. The authors emphasised the necessity of identifying risks factors for aspiration early and suggested that clinical screening methods are needed to recognise patients with oropharyngeal dysphagia. However, swallowing clinical screening performed by speech therapists and nurses is a standard of care in critical care units. This concept is particularly relevant, considering that in stroke patients, the prognosis is closely related to the medical complications, and aspiration is responsible for >50% of these and increases mortality for up to 33% at 6 months. Even more, after the acute phase of a stroke, swallowing dysfunction has a recovery capacity of 87% at 6 months [4–6]. The three-ounce water test is a well-known and useful bedside screening tool for oropharyngeal dysphagia http://ow.ly/9Krl30cW2HJ